Greenwash Online Marketing: Does Indonesian Gen-Z Still Have The Intention To Repurchase Green Products? - Valendia, Ida Ayu Saras; Purwanegara, Mustika Sufiati (School of Business, IPB University (SB-IPB), 2022)
This research was conducted to know whether Gen-Z in Indonesia still has the intention to buy bottled drinking water after knowing the term greenwash marketing by looking at the mediating effect of environmental concern and perceived quality. The study was conducted using a survey method of 160 Gen-Z respondents in Indonesia and analyzed using SmartPLS. From the research results, there is no significant relationship between greenwash perception and environmental concern with Gen-Z's intention to repurchase bottled drinking water products. However, the relationship between greenwash perception and environmental awareness and quality perception of Gen-Z's intention to repurchase bottled drinking water products was significant. Managers are also expected to focus more on maintaining the quality of bottled drinking water by paying more attention to the environment because clean water can only be obtained if natural preservation and ecosystem balance are correctly maintained, thus avoiding the impression of greenwash marketing in online media. Keywords: Greenwash marketing, environmental concern, perceived quality, repurchase intention, Gen-Z